Inscription, Seth Samaldas Narsidas pyaav - Ghosh, Ayan (2023)
Inscribed in English within an arched niche, the name of the pyaav and its erection for public use by Javerbai, widow of Seth Narsidas Devidas, in memory of her son Seth Samaldas Narsidas. The year of installation (1903) is mentioned at the bottom. The Gujarati translation is inscribed on the opposite face of the pyaav.